2001
DOI: 10.1002/ajim.1123
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to pesticides: A feasibility study among migrant and seasonal farmworkers

Abstract: We documented the feasibility of following farmworkers to assess in utero exposure to pesticides and other contaminants, and demonstrated exposure to these compounds. Difficulties in measuring pesticides with short half lives were noted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Another large study of 125 spouses of farmer applicators observed that most of the individuals were below 1 ppb (Arbuckle & Ritter, 2005). Other studies of women reported the geometric mean 2,4-D level to be 1 pbb or less (Harris et al, 1992; Cooper et al, 2001; Alexander et al, 2007). The monitoring levels of bystander children were slightly higher than the parents (Arbuckle et al, 2004; Alexander et al, 2007; Arcury et al, 2007).…”
Section: Review Of Urinary Biomonitoringmentioning
confidence: 97%
“…Another large study of 125 spouses of farmer applicators observed that most of the individuals were below 1 ppb (Arbuckle & Ritter, 2005). Other studies of women reported the geometric mean 2,4-D level to be 1 pbb or less (Harris et al, 1992; Cooper et al, 2001; Alexander et al, 2007). The monitoring levels of bystander children were slightly higher than the parents (Arbuckle et al, 2004; Alexander et al, 2007; Arcury et al, 2007).…”
Section: Review Of Urinary Biomonitoringmentioning
confidence: 97%
“…Endosulfan has also been detected from human tissues. It has been detected from cord blood samples obtained at the time of delivery [19] human sera [72,73], adipose tissue [74] and human milk samples obtained from healthy lactating women in Spain [75], human breast milk from Egypt, Colombia and Nicaragua [76]. High levels of endosulfan were detected in human breast milk in Sub Saharan Africa and also from India [77].…”
Section: Endosulfan Residue In Kola Nutsmentioning
confidence: 99%
“…Endosulfan has also been detected from human tissues. It has been detected from cord blood samples obtained at the time of delivery [19]. There is experimental evidence of adverse effects of endosulfan on the male reproductive system, delaying sexual maturity and interfering with the sex-hormone synthesis [20].…”
Section: Introductionmentioning
confidence: 99%
“…Higher concentrations of endosulfan was reported in bovine fat [75] and cattle meat [65] . Varying levels of endosulfan concentrations have been reported in cow milk Cisato et al, human tissues and cord blood samples [18] , adipose tissue [5] and human breast milk samples [16] , [84] , [81] .…”
Section: Resultsmentioning
confidence: 99%